Distress Severity Following a Romantic Breakup Is Associated With Positive Relationship Memories Among Emerging Adults. (August 2017) - del Palacio-González, Adriana; Clark, David A.; O'Sullivan, Lucia F.
Romantic relationship loss is associated with significant psychological distress for emerging adults. Intrusive memories of stressful events are typically associated with symptom severity; however, whether spontaneous positive memories of a relationship breakup may also be related to psychological symptoms has received little attention. We examined links between breakup-specific distress, depressive symptoms, and relationship memories of different valence. Ninety-one emerging adults ( M age = 20.13) who had experienced a recent romantic breakup recorded the frequency of positive and negative spontaneous relationship memories in a 4-day online memory diary. Control memories were also recorded. Positive memories were specifically related to breakup distress, whereas negative memories were related to both breakup distress and depression. No such associations were found for the control memories. Experiences of positive memories appear critical for understanding the degree of distress a young person may experience following a breakup. Possible explanations for these findings and similarities with the grief and bereavement literature are discussed.